Endoscopic ultrasound-guided gallbladder drainage for acute cholecystitis with a silicone-covered nitinol short bilaterally flared stent: a case series - Raffaele Manta; Claudio Zulli; Angelo Zullo; Edoardo Forti; Alberto Tringali; Lorenzo Dioscoridi; Francesco Zito; Helga Bertani; Rita Conigliaro; Massimiliano Mutignani (Endoscopy International Open, 2017)
Background and study aim Gallbladder drainage in patients with cholecystitis who are unsuitable for surgery may be performed by endoscopic ultrasound (EUS)-guided placement of specifically designed fully covered metal stents. We describe the first case series of patients treated with a silicone-covered nitinol stent with bilateral anchor flanges. Patients and methods Data from consecutive patients with acute cholecystitis who were deemed unsuitable candidates for surgery were collected. The stent placement procedure was performed in two tertiary endoscopy centers by four experienced endoscopists. Technical and clinical success rates, as well as adverse events and clinical outcome at follow-up, were assessed. Results EUS-guided drainage for cholecystitis was performed in 16 patients (mean age 84 years; nine males). Technical and clinical success rates were 100 % (16/16) and 94 % (15/16), respectively; an early failure due to stone impaction occurred in the remaining case and required placement of a new stent. Symptom relief occurred in 11/15 cases (73 %) within 1 day, and within 2 days in the remaining 4 patients. Bleeding occurred in two patients (13 %): in one patient intraprocedural bleeding was successfully stopped during endoscopy; and delayed bleeding occurred in one patient requiring arterial embolization for catastrophic bleeding (patient died 10 days later). No cases of cholecystitis recurrence or biliary obstruction were observed during a median follow-up of 112 days (range 49 – 180 days). Conclusions Our data showed that EUS-guided gallbladder drainage with a specially designed stent is feasible and successful in patients with acute cholecystitis who are unfit for surgery.